(3LhGH KeGfjI hKdGKjf SDGdkG hQOJ Edi GdEeGe jMji Hf MeRI Hf Ydi GdYdhis - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdSDGd GdChd (B: (3eG jQi ehdGfG CejQ GdeDefjf hEeGe GdeSdejf jMji Hf MeRI s
(3BNQgG (B:s
(3BNQg ai GdSDGd GdKGef hGdKdGjf bhdg (B: (3EPG cGf Ydi GdJQGVi hGdTQY JaUd GdNUheI JeJ GdSDGdGJ hCLhHJgG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGefs
(3HBNQgG SeGYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdLGeY GdcHjQ HUfYGA (B((3eLGejY (B10) s
Keywords: (3abg GdePGgH GdCNQis